Watching Teacher Candidates Watch Themselves: Reflections on a Practicum Program in Turkey - Sumru Akcan (Universidad Nacional de Colombia, 2010)
This article presents the findings of a study that investigates pre-service English teachers' reflections on their teaching performance after watching their videotaped lessons in company with their university supervisor. This study, conducted during the spring semester practicum program in the 2007-2008 academic year, examines how the teacher candidates felt about their teaching while watching a video of a real lesson taught in a classroom. The findings of this study suggest that after the teacher candidates watched their own teaching with the supervisor, they made specific comments about teacher talk and about students' participation and interest in the lesson. The findings also show that the use of video recording in the practicum program provided opportunities for reflection and helped teacher candidates evaluate their performance more critically.